A The Public Interest Implications (Maslahah) of The OJK's Regulatory Amendments Pertaining To Islamic Peer-To-Peer Lending In Indonesia. - Zikry , Farhan; Intan, Makhda Intan Sanusi; Basri, Ahmad Hasan (Ijtihad, 2024)
**English**This study discusses the regulatory changes concerning Sharia-based peer-to-peer lending, specifically the transition from POJK No. 77 of 2016 to POJK No. 10 of 2022. A significant aspect of this change is the inclusion of several articles that accommodate Sharia-based peer-to-peer lending transactions. These regulatory amendments indicate that the Sharia principles embedded in the regulation promote public welfare (maslahah). Therefore, the author seeks to examine this issue from the perspective of maqasid asy-syari’ah. This research focuses on textual and literature analysis, utilizing a library research method, and adopts a normative approach based on religious norms. The result of this study suggest that, from the perspective of maqasid asy-syari’ah, the changes made by the Financial Services Authority (OJK) to the regulations on peer-to-peer lending foster public welfare, which is evaluated based on the five essential objectives (al-daruriyyat al-khams): the preservation of religion (hifz al-din), life (hifz al-nafs), intellect (hifz al-‘aql), lineage (hifz al-nasl), and wealth (hifz al-mal).                                                           **Indonesia**Penelitian ini akan mendiskusikan tentang adanya perubahan regulasi tentang peer to peer lending berbasis syariah yakni POJK No.77 Tahun 2016 yang kemudian digantikan dengan POJK Nomor 10 tahun 2022. Hal yang signifikan yang dapat dilihat dari perubahan ini adalah beberapa pasal yang cukup akomodatif terhadap transakasi peer to peer lending berbasis syariah. Dengan adanya perubahan regulasi tersebut dindikasikan bahwa konsep syariah pada peraturan tersebut menimbulkan kemaslahatan, sehingga penulis ingin mengulsnya dari sudut pandang maqasid asy-syari‘ah. Penelitian ini berfokus pada analisis teks dan literatur library research atau studi kepustakaan dan penelitian ini menggunakan pendekatan normatif, yang berlandaskan norma-norma keagamaan. Dalam penelitian ini menghasilakan temuan bahwa dalam perspektif maqasid asy-syari‘ah perubahan yang dilakukan OJK dalam peraturanya tentang peer to peer lending menimbulkan kemaslahatan yang diukur dari Al-daruriyat al-khams  (hifz al-din; hifz al-nafs; hifz al-‘aql; hifz al-nasl; dan hifz al-mal).